Ambulatory gas exchange measurements - Current status and future options - Meyer, T.; Davison, R. C. R.; Kindermann, W. (International Journal of Sports Medicine, 2005)
This article summarizes the scientific literature on portable devices used for the measurement of gas exchange during exercise. Firstly, the results from validity investigations are reviewed in terms of accuracy, reliability, and influence of additional weight during field testing. On the basis of these findings, at least two of the most often tested portable devices, MetaMax I/II and K2/K4 b2, can be regarded as valid, with their results not differing substantially from (stationary) metabolic carts. The second part of the article provides an overview of ambulatory gas exchange applications which have been investigated so far. There is a number of descriptive (cross-sectional) studies that characterize the physiological profiles of different sports. In addition, some diagnostic tests of functional capacity have been validated, and a few investigations have assessed nutritional interventions and their effect on metabolism. Some indicate potential future directions including an evaluation of the efficacy of modifying metabolic pathways during exercise, e. g. by specifically designed training. Also, the extension of descriptive/cross-sectional investigations to typical training sessions will be worthwhile.